Evaluation of the Effectiveness of Psychoeducation Given to Children with Parental Psychiatric Disorders. (1st November 2020) - Küçük, Leyla; Bilgin, Hülya; Çömez Ikican, Tuba; Kaçar, Selma; Kadak, Muhammed Tayyip; Demirel, Ömer Faruk; Çoban, Vahdi; Kutlu, Fatma Yasemin; Aksoy Poyraz, Cana; Buzlu, Sevim; Duran, Alaattin
Abstract: This study was aimed to determine the effectiveness of psychoeducation program which was developed to improve the coping skills and to increase the psychological resistance of 12–18 years children/adolescents whose parents' have psychiatric disorders. The study was carried out between May 2018 - November 2019 with children of patients who applied to the outpatient clinic and inpatient treatment at Istanbul University – Cerrahpasa, Cerrahpasa Faculty of Medicine Department of Psychiatry. Total of 40 children (experiment = 20 and control = 20), participated in the study. Data were collected using Personal Information Form, Adolescent Psychological Resilience Scale and Kidcope. The mean age of the children/adolescents in the experimental group was 14.05 ± 1.90, 50% was male and the mean age of the control group was 15.35 ± 2.08, and 55% were male. It was determined that the mean duration of psychiatric disorders were 11.50 ± 6.39 years and 40% of the psychiatric diagnosis was schizophrenia in the experimental group, and the mean duration psychiatric disorders were 6.10 ± 5.16 years and 30% of the psychiatric diagnosis was a depression in the control group. After psychoeducation, the total scores of scales in the experimental group showed an increase compared to the control group and a significant difference in a statistical context. It was found that children/adolescents participating in the psychoeducation program had increased psychological resilience levels and improved coping skills. This result shows that the psychoeducation program for children/adolescents with psychiatric disorders in their parents is effective.